Fiber lasers and their applications [Invited] - Shi, Wei; Fang, Qiang; Zhu, Xiushan; Norwood, R A; Peyghambarian, N (Applied optics. Optical technology and biomedical optics, 2014)
Fiber lasers have seen progressive developments in terms of spectral coverage and linewidth, output power, pulse energy, and ultrashort pulse width since the first demonstration of a glass fiber laser in 1964. Their applications have extended into a variety of fields accordingly. In this paper, the milestones of glass fiber laser development are briefly reviewed and recent advances of high-power continuous wave, Q-switched, mode-locked, and single-frequency fiber lasers in the 1, 1.5, 2, and 3 μm regions and their applications in such areas as industry, medicine, research, defense, and security are addressed in detail.